Immigration and British Politics from 1980s onwards - BAROUD, Fatima Zahra; AFKIR, Mohammed (Faculty of Letters and Foreign Languages Department of English, 2018)
The contribution of immigrants in British politics is backdated to the pre-war era. In the recent decades, this contribution is strikingly different due to the government‟s attempts to restrain the power of immigrants. However, they constitute a vehement opponent as they manage to impose themselves. This policy adapted by the government became more visible after 9/11 Attacks when they started considering Muslims as an imminent danger. Surprisingly, this incident constitutes a spark for the Muslim activisim to be more effective in the 21th C. They change the rule of the game and contribute in the emergence of new political entities. This paper investigates different patterns of immigrants‟ political involvement either as electorates or candidates, in addition to the political movements, organizations and election campaigns that worked on urging these communities. The first chapter is concerned with the historical context to immigration and British politics and the roots of immigrants‟ political involvement in this country, because it is worth to mention the various stages of its development. The second chapter investigates their political engagement in the 1980s and 1990s, the main problems they faced and the way how they dealt with. The third chapter is devoted to be on Muslim involvement in British politics and how they faced the campaign organized against them after 9/11. It depicts their situation in the wake of this incident and their strategies to improve their image. Overall, this research concludes that the social problems cannot be solved by accusing immigrants and alienating them. In contrast, involving them in the political life will make them feel responsible and work hand in hand with government to get rid of all these problems